Crystal Balls and Black Boxes: What Makes a Good Forecast?. (August 2019) - Voulgaris, Carole Turley
As a discipline that concerns itself with the future, planning relies on forecasts to inform and guide action. With this reliance comes a concern that the best possible forecasts be produced. This review identifies three distinct ways in which forecasts may be evaluated (methodology, accuracy, and usefulness) and describes challenges associated with evaluating forecasts along any of these three dimensions. By way of example, this general discussion of forecasting is applied to the specific case of demand forecasts for transportation infrastructure, with an emphasis on transit infrastructure. There is a continuing need for planners to engage with interdisciplinary forecasting literature.